2019
DOI: 10.2147/opth.s205352
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinically relevant differences in the selection of toric intraocular lens power in normal eyes: preoperative measurement vs intraoperative aberrometry</p>

Abstract: Purpose: To assess the value of intraoperative aberrometry (IA) in determining toric intraocular lens (IOL) power in eyes with no previous ocular surgery. Patients and methods: This was a retrospective data review at one US clinical site of eyes that underwent uncomplicated cataract surgery with toric IOL implantation where standard preoperative and IA measurements were available. Calculated IOL sphere and cylinder powers and orientation were compared based on the measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Keratometers, corneal topographers, anterior segment tomographers, and intraoperative aberrometers can each provide corneal measurements necessary to accurately predict the ideal IOL cylinder power and alignment meridian to correct astigmatism during cataract surgery [ 6 ]. Since each device has its own characteristics, measurements obtained from different devices may not be comparable due to different refractive indices or measurement areas being used.…”
Section: Introductionmentioning
confidence: 99%
“…Keratometers, corneal topographers, anterior segment tomographers, and intraoperative aberrometers can each provide corneal measurements necessary to accurately predict the ideal IOL cylinder power and alignment meridian to correct astigmatism during cataract surgery [ 6 ]. Since each device has its own characteristics, measurements obtained from different devices may not be comparable due to different refractive indices or measurement areas being used.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that cataract surgery with intraoperative aberrometry achieves low postoperative residual astigmatism [5,14,37,52,[62][63][64][65][66][67][68], including multiple studies in which intraoperative aberrometry was shown to achieve lower postoperative residual astigmatism than preoperative measurements [5,14,52,62,67,68] and studies in which intraoperative aberrometry achieved a larger proportion of patients with residual astigmatism less than 0.5D [67,68]. Of note, several studies using the Barrett toric calculator (which incorporates posterior corneal astigmatism) have not shown lower postop residual astigmatism in intraoperative aberrometry relative to preoperative calculations [37,69,70]; however, other studies utilizing the Barrett toric calculator have shown lower postop residual astigmatism in intraoperative aberrometry [67,68]. One study also found that computer-assisted registration utilizing the Zeiss Callisto Eye achieved lower postop residual astigmatism than intraoperative aberrometry [61].…”
Section: Toric Intraocular Lensesmentioning
confidence: 99%
“…Moreover, in studies with broad cohorts, overall outcomes are generally not reported, and instead the focus is on subsets of patients [20 ▪▪ ,28 ▪ ]. In contrast, there are numerous studies that instead focus on either routine/typical non-post-refractive surgery cases alone [6,9,10 ▪ ,11,14,30–32,33 ▪ ,34–38] or on subsets of atypical patients [29,39–52]. This trend in publications may be at least in part a reflection that in the real world, many cataract surgeons utilize intraoperative aberrometry selectively rather than broadly.…”
Section: Broad Use Of Intraoperative Aberrometry For All-comersmentioning
confidence: 99%
“…1 Nevertheless, they require additional effort, including preoperative measurement, planning, and modifications in intraoperative techniques. [2][3][4][5][6][7] Previous studies have reported good visual and refractive outcomes, which are an important part of the standard of care for astigmatism correction with cataract surgery, especially in higher degrees of astigmatism. [8][9][10][11][12] This procedure is also ideal for patients with regular astigmatism who hope to reduce their dependence on glasses for distance vision.…”
Section: Introductionmentioning
confidence: 99%